Student teachers’ and teacher educators’ pedagogical reflections on piano courses in Finnish primary school teacher education. - Sepp, Anu; Ruismäki, Heikki; HIetanen, Lenita (SAGE Publications Ltd, 2023)
Reflection is a key component in teachers' educational programs. As teachers transfer human values through the subject(s) they teach, their pedagogical thinking plays an essential role in decision-making. As part of the Arctic Reformative and Exploratory Teaching Profession (ArkTOP) project (Finland), this case study examines the potential for developing pedagogical thinking in the education of primary school teachers. The aim of this study was to identify the levels of pedagogical thinking in students and educators through studying their reflections on piano courses. The results indicated that student teachers reflected on an action level rather than upon metatheory. Teacher educators shared reflections from both an object theory and metatheory level, while the student teachers' reflections were focused on their individual skills when making music. Thus, teacher educators should offer student teachers more guidance on how to reflect upon their activities and provide argumentation for their possible pedagogical decisions. Peer reviewed